Prestressed concrete transmission pole structures : recommended practice for design and installation - Oliphant, Wesley J.; Sherman, Douglas C. (American Society of Civil Engineers, 2012)
Prepared by the Task Committee on Concrete Transmission Pole Structures of the Committee of Electrical Transmission Structures of the Structural Engineering Institute of ASCE. Prestressed Concrete Transmission Pole Structures: Recommended Practice for Design and Installation is a complete engineering reference on static-cast and spun-cast prestressed concrete poles for electric distribution and transmission power lines. This Manual of Practice contains critical information for all aspects of a prestressed concrete pole project, including applications, concepts, materials, connections, foundations, manufacture, installation, and testing. Topics include: considerations for the design process; specifications for concrete and steel materials; design choices, criteria, and methodology; quality assurance during manufacture; assembly and erection; and inspection, maintenance, and repair. Appendixes offer sample documents showing specifications for the purchase of static and spun cast prestressed concrete poles. Utility engineers responsible for the design of transmission and distribution lines, pole manufacturers, power line constructors, and inspectors will find this manual to be useful for basic training and as an ongoing reference.
Keywords: Electric lines -- Poles and towers -- Design and construction.; Electric lines -- Poles and towers -- Installation.; Prestressed concrete poles -- Design and construction.; Prestressed concrete poles -- Installation.; elektronické knihy; electronic books